2018
DOI: 10.4028/www.scientific.net/amm.877.248
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Quarry Dust as a Partial Replacement of Fine Aggregate in Self Compacting Concrete

Abstract: Large quantity of the quarry dust gets produced annually in the quarries during the extraction of the crushed coarse aggregate. As a result, disposal problems of this material gain significant momentum as these disturb environmental systems also. Now-a-days many of the countries like India is facing problems of ban on the extraction of sand and lacunae in procuring of fine aggregate, which is important constituent of the concrete. To overcome this problem, present study is focused on the suitability to utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Mundra S, et.al prepared concrete mixes to measure compressive strength in the presence of Quarry dust which has different proportions, and found that 30% replacement has higher strength [15]. Arpitha D, et.al performed the experiment on a different percentage of quarry dust and found that at 15% replacement compressive strength increased by 2% [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mundra S, et.al prepared concrete mixes to measure compressive strength in the presence of Quarry dust which has different proportions, and found that 30% replacement has higher strength [15]. Arpitha D, et.al performed the experiment on a different percentage of quarry dust and found that at 15% replacement compressive strength increased by 2% [16].…”
Section: Introductionmentioning
confidence: 99%